The Role of Financial Literacy and Financial Technology on the Decision to Use Pay Later Moderated by Hedonism Lifestyle - Pratiwi, Windi; Ariffin, Muchammad (Yayasan Riset dan Pengembangan Intelektual, 2025)
Fintech is rapidly growing in various sectors such as payment start-ups, lending, financial planning, retail investment, financing, remittances, and financial research. Many start-up apps use pay-later payment services, so it is important to consider the consequences without a good financial understanding. Fintech plays an important role in effective payment transactions and has become part of the hedonistic lifestyle, increasing people's consumptive behavior. Financial literacy and fintech play a role in the decision to use PayLater services in Pontianak City, with financial literacy contributing positively at 27.8% and fintech at 53.1%. Although a hedonic lifestyle does not moderate the relationship between financial literacy and PayLater usage, it still has a positive effect of 22.2%. Overall, financial literacy, fintech, and lifestyle have a significant role in the decision to use PayLater in Pontianak City.